The Role of Culture and Contextual Risk for Maternal Parenting and Children's Behavior Regulation in Chile and Germany. - Deffaa, Mirjam; Weis, Mirjam; Muñoz, Lorena; Trommsdorff, Gisela (Journal of Child & Family Studies, 2022)
Children's behavior regulation development takes place in diverse sociocultural settings. In this study, we take a multilayer ecological perspective and examine cross-cultural as well as intra-cultural similarities and differences in relations between different aspects of contextual risks (i.e., family and neighborhood risk), maternal restrictive control, and children's behavior regulation in Chile and Germany. One hundred sixty-seven mothers of primary school children in Chile and 109 mothers in Germany (total sample M (child age) = 10.01 years) completed questionnaires on family risk, parenting practices, and their child's behavior regulation. Mothers in Germany rated children's behavior regulation significantly higher than mothers in Chile. Further, in both cultural contexts (Chile, Germany), the higher the family risk, the higher was the use of maternal restrictive control and the lower the child's behavior regulation. In Chile, after including maternal restrictive control, the relation between family risk and children's behavior regulation remained significant. In Germany, in contrast, there was no direct significant relation between family risk and children's behavior regulation, instead we found a significant indirect pathway via maternal restrictive control. Further, we investigated the moderating role of neighborhood risk, as distal contextual risk, for the relation between family risk and maternal restrictive control as well as for the relation between maternal restrictive control and children's behavior regulation. We found no significant overall moderated mediation effect. However, findings in Chile and Germany revealed a conditional indirect effect indicating that family risk and behavior regulation were indirectly related via maternal restrictive control only when neighborhood risk was high. This underlines the need for an integrative consideration of the cultural context as well as family risk and neighborhood risk when investigating the role of maternal parenting for children's behavior regulation development. Highlights: This study takes an ecological perspective to investigate multilayer contextual aspects in relations between distal and proximal aspects of contextual risk, maternal parenting, and children's behavior regulation in Chile and Germany. In both cultural contexts studied, we found that the higher family risk was, the higher was the reported maternal restrictive control and the lower children's behavior regulation. In Chile, family risk and children's behavior regulation were related directly as well as indirectly via maternal restrictive control. In Germany, family risk and children's behavior regulation were not related directly but indirectly via maternal restrictive control.